Utilização da casca da castanha de caju Anarcadium occidentale L. como biossorvente de metais - Coelho, Gustavo Ferreira (2014)
This study proposes evaluate the use of chasew nut s shell (Anarcadium occidentale L.) CNS - as a natural adsorbent on the removal of metallic ions Cd2+, Pb2+, Cr3+, Cu2+ and Zn2+ from aqueous medium, as alternative to activated carbon and other treatments. The cashew nut was collected in Curionópolis, in the state of Pará, where experiment was performed at the Laboratory of Environmental Chemistry and Instrumental of UNIOESTE Marechal Cândido Rondon, Paraná. After the extraction of liquid by the cashew nut s shell (LCNS) the adsorbent was characterized as its chemical composition, structural, by infrared spectroscopy (IR), morphological, by scanning electron microscopy (SEM), and point of zero change (pHPCZ). Thereafter were made tests to determine the influence of pH, mass of adsorvent, contact time, initial concentration and temperature and also to determine the optimal conditions of adsorption.The adsorption kinetics was evaluate thought mathematics models of pseudo first, pseudo second order, Elovich and diffusion intraparticle, and the adsorption isotherma were linearized as the mathematics models of Langmuir, Freundlich and Dubinin-Radushkevich (D-R). Lastly was held the desorption and the comparison with activated carbon. Was observed by MEV that the CNS showed aspect lamella, spongy, irregular structure and heterogeneous, and by IR may be the presence hydroxyl groups, aliphatic, phenolic, carboxylic acid, in both analyzes confer to adsorbent characteristics favorable to adsorption. The pHPCZ of CNS is between 3,69 and 4,01. The adsorbents mass; 12 g L-1 and contact time of 60 min. The pseudo second order models and D-R suggested the predominance of chemiosorption on process. The adjust of Langmuir and Freundich moldels suggested the occurrence of adsorption as in mono as multilayers. The thermodynamic study demonstrated that the process was only spontaneous for the Cd2+ in 15 e 25 ºC. The CNS presented high rate os desorption of Cd2+ and Pb2+, being only the Cr3+ what presented low rate of desorption. Concerning the ions Cu2+ and Zn2+ the optimal condition of adsorption were pH of solution 4,0 and 5,0 respectively; mass of CNS: 8 g L-1 and contact time of 60 min. The Cu2+ for the CNS adjusted itself for models of pseudo second order, Langmuir suggesting chemisorptions and adsorption in monolayers and the D-R model in which fisiosorption suggested. The Zn2+ adjusted itself by pseudo second order models, D-R. Langmuir and Freundlich, suggesting chemical adsorption and in mono and multilayers. The enthalpy values (ΔH) suggested physisorption. The biosorbent observed lower efficiency of adsorption that the CA, however the desorption efficiency was much greater suggesting the possibility of reuse of biosorbent for removal of Cu2+ and Zn2+. In this manner it can be conclude that the CNS has potential for add economic value and increase the production chains of the culture, when this residue utilized for removal of Cd2+, Pb2+, Cr3+, Cu2+ and Zn2+ of contaminated waters